2018
DOI: 10.1016/j.buildenv.2017.11.041
|View full text |Cite
|
Sign up to set email alerts
|

A wind tunnel study of effects of twisted wind flows on the pedestrian-level wind field in an urban environment

Abstract: The influence of twisted wind flows on the pedestrian-level wind (PLW) field of an urban area was evaluated by testing a typical urban site (Tsuen Wan, Hong Kong) in a boundary layer wind tunnel. Four twisted wind profiles with different magnitudes and directions of yaw angles were employed to investigate variations in wind speed with the properties of the twisted wind flows at the pedestrian level. An additional conventional wind profile with similar wind speeds and turbulence intensities to the twisted winds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Two twisted wind profiles and a conventional wind profile were employed as approaching wind profiles for the detailed AVA test. The two twisted wind profiles were simulated using a novel vane system originally developed by Tse et al [12] and were proven to be having consistent wind speeds and turbulence intensities to conduct successful pedestrian-level wind tunnel studies as reported previously [15][16][17]. Fig.…”
Section: The Wind Tunnel Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two twisted wind profiles and a conventional wind profile were employed as approaching wind profiles for the detailed AVA test. The two twisted wind profiles were simulated using a novel vane system originally developed by Tse et al [12] and were proven to be having consistent wind speeds and turbulence intensities to conduct successful pedestrian-level wind tunnel studies as reported previously [15][16][17]. Fig.…”
Section: The Wind Tunnel Experimentsmentioning
confidence: 99%
“…In addition, the hilly terrain of Hong Kong frequently produces twisted wind profiles: at different heights within the profile winds have various directions [12][13][14]. The authors of this paper have used twisted wind profiles in a series of wind tunnel tests on isolated buildings [16], arrays of buildings [16], and a real urban area [17], and have demonstrated the profiles' considerable influence on the PLW fields in built-up areas. This influence is even more critical on AVA as reported by Tse et al [12] after analysing data of 256 wind profiles obtained from 13 previous AVAs.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some researchers have utilized "around buildings" arrangements to study a wind environment around buildings [19,22,23] (Figure 1c). Some researchers have utilized "distributed" arrangements to perform the wind environment assessment for built-up areas [24,25] (Figure 1d). In the wind tunnel experiments, authors have used different arrangements of measurement points for different research objectives [18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have utilized "distributed" arrangements to perform the wind environment assessment for built-up areas [24,25] (Figure 1d). In the wind tunnel experiments, authors have used different arrangements of measurement points for different research objectives [18][19][20][21][22][23][24][25]. These four main arrangements of measurement points take into consideration some urban spatial characteristics (such as streets), but because their research purpose is not based on the characteristics of the urban space, the arrangements do not fully reflect the characteristics of the urban space.…”
Section: Introductionmentioning
confidence: 99%